2014
DOI: 10.1002/mrd.22339
|View full text |Cite
|
Sign up to set email alerts
|

SUMO‐1 plays crucial roles for spindle organization, chromosome congression, and chromosome segregation during mouse oocyte meiotic maturation

Abstract: Small ubiquitin-related modifier-1 (SUMO-1)-dependent modifications of many target proteins are involved in a range of intracellular processes. Previous studies reported the localization of SUMO-1 during oocyte meiosis, and that overexpression of Sentrin/SUMO-specific protease 2 (SENP2), a de-SUMOylation protease, altered SUMO-modified proteins, and caused defects in metaphase-II spindle organization. In this study, we detailed the consequences of SUMO-1-mediated SUMOylation by either inhibition of SUMO-1 or U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…However, SUMO is not essential for SC assembly in early pachytene in nematodes (Bhalla et al., 2008) and localizes mainly at the midbivalent, where key regulators of chromosome congression (like KLP-19) reside. As in nematodes, it has been shown in rat spermatocytes that SUMO does not co-localize with the synaptonemal complex during pachytene (Rogers et al., 2004), while depletion of SUMO or UBC9 caused abnormal spindle organization, and led to chromosome misalignment, segregation defects, and aneuploidy in rat oocytes (Yuan et al., 2014). Additionally, SUMO-1 concentrates in spindle poles and between segregating chromosomes in anaphase I, while SUMO-2/3 co-localized with condensed chromatin in mouse oocytes (Wang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, SUMO is not essential for SC assembly in early pachytene in nematodes (Bhalla et al., 2008) and localizes mainly at the midbivalent, where key regulators of chromosome congression (like KLP-19) reside. As in nematodes, it has been shown in rat spermatocytes that SUMO does not co-localize with the synaptonemal complex during pachytene (Rogers et al., 2004), while depletion of SUMO or UBC9 caused abnormal spindle organization, and led to chromosome misalignment, segregation defects, and aneuploidy in rat oocytes (Yuan et al., 2014). Additionally, SUMO-1 concentrates in spindle poles and between segregating chromosomes in anaphase I, while SUMO-2/3 co-localized with condensed chromatin in mouse oocytes (Wang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…SENP1 is a protease that appears to be localized in several compartments and deconjugates a large number of SUMOylated proteins [1820]. Recently, protein post-translational modification SUMOylation has been reported to play an important role in germ cell function, especially in mammalian meiosis [2123]. Several studies have characterized expression of SUMO-1 and SUMO-2/3 in oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…While SUMO-2/3 proteins are localized in nucleoplasm, SUMO-1 is concentrated at spindle organization and chromosome in transcriptionally active oocytes with little location on nuclear membrane in quiescent oocytes. Moreover, this specific localization of SUMO-1 plays a critical role during oocytes maturation [2123]. It has also been reported that differential localization of SENP1 regulate SUMOylation in a temporal and spatial fashion along the oocyte meiosis procession [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…The results are consistent with a missegregation of MIC chromosomes during mitosis. The requirement for SUMOylation in chromosome segregation is well established for other species (48)(49)(50)(51). In budding yeast, deletion of UBC9 results in gross defects in chromosome structure and integrity as well as aberrant segregation and polyploidy (15).…”
Section: Discussionmentioning
confidence: 99%